2D Few-Layered PdPS: Toward High-Efficient Self-Powered Broadband Photodetector and Sensors - Roy, Pradip Kumar; Antonatos, Nikolas; Li, Tianchun; Jing, Yu; Luxa, Jan; Azadmanjiri, Jalal; Marvan, Petr; Heine, Thomas; Sofer, Zdenek (ACS Applied Materials and Interfaces, 2022)
Photodetectors and sensors have a prominent role in our lives and cover a wide range of applications, including intelligent systems and the detection of harmful and toxic elements. Although there have been several studies in this direction, their practical applications have been hindered by slow response and low responsiveness. To overcome these problems, we have presented here a self-powered (photoelectrochemical, PEC), ultrasensitive, and ultrafast photodetector platform. For this purpose, a novel few-layered palladium-phosphorus-sulfur (PdPS) was fabricated by shear exfoliation for effective photodetection as a practical assessment. The characterization of this self-powered broadband photodetector demonstrated superior responsivity and specific detectivity in the order of 33 mA W-1 and 9.87 × 1010 cm Hz1/2 W-1, respectively. The PEC photodetector also exhibits a broadband photodetection capability ranging from UV to IR spectrum, with the ultrafast response (∼40 ms) and recovery time (∼50 ms). In addition, the novel few-layered PdPS showed superior sensing ability to organic vapors with ultrafast response and a recovery time of less than 1 s. Finally, the photocatalytic activity in the form of hydrogen evolution reaction was explored due to the suitable band alignment and pronounced light absorption capability. The self-powered sensing platforms and superior catalytic activity will pave the way for practical applications in efficient future devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: band bending; broadband; photocatalytic; photoelectrochemical (PEC) photodetector; vapor sensor